Hydrological assessment of different satellite precipitation products in semi-arid basins in Morocco - El Khalki, El Mahdi; Tramblay, Yves; Saidi, Mohamed Elmehdi; Marchane, Ahmed; Chehbouni, Abdelghani (Frontiers in Water, 2023)
In data-sparse regions and in developing countries such as Morocco, where flooding has serious socioeconomic impacts, satellite-based precipitation products open new possibilities for monitoring and modelling water resources and floods. The objective of the study is to explore the possibility of using satellite precipitation products (SPPs) with hydrological models (CREST and MISDc) over 9 basins in Morocco. This work provides a hydrological assessment of three SPPs that have demonstrated good capabilities in reproducing precipitation over different basins in Morocco (GPM IMERG -PERSIANN CDR (PERCDR) and CHIRPS). The two hydrological models are coupled with a stochastic calibration method to provide the different ranges of uncertainties. In addition, we investigate the ability of SPPs on reproducing the November 2014 flood event that affected a large part of Morocco. The results indicated that, in calibration, both hydrological models provided similar performance to reproduce river discharge with observed precipitation or PERSIANN CDR. In validation, the combination of the MISDc model with PERSIANN CDR performed the best, notably allowing a good simulation of the flood hydrographs during the November 2014 event. The analysis of relationships between SPPs, basin properties, and hydrological modelling technique will allow to find the appropriate combination for different application purposes.